21st Century Learning Transformation: Systematic Review Literacy-Numeracy Enhancement Strategies Senior High School Students - Anita Dewi Utami; Cholis Sa'dijah; Intan Sari Rufiana; Muhammad Kharis; Novi Rahmadhani Putri; Mohamad Aminudin (JURNAL PENDIDIKAN MATEMATIKA, 2025)
Abstract. In the context of 21st-century education challenges, literacy and numeracy remain foundational competencies for high school students, yet global assessments consistently reveal significant gaps in these skills. This systematic review aims to identify and analyze evidence-based strategies for improving literacy and numeracy among senior high school students. The review synthesizes findings from 15 empirical studies published between 2019-2024 sourced from Scopus, ERIC, and Google Scholar using keywords such as 'literacy numeracy improvement,' 'senior school students,' and 'educational strategies.' Data were analyzed using a thematic analysis approach of qualitative and quantitative studies. The findings highlight four effective approaches: (1) technology-enhanced learning (adaptive platforms), (2) contextualized pedagogy (such as project-based learning), (3) targeted teacher training, and (4) cross-curricular integration. These four strategies were shown to provide measurable improvements to student learning outcomes. The study concludes that a multifaceted, evidence-driven approach, combining these strategies with multidisciplinary collaboration is essential for meaningful and sustainable progress in addressing literacy-numeracy deficits, particularly when adapted to local educational contexts.Keywords: Literacy, numeracy, senior high school students